Penyuluhan Bahasa Inggris Dasar Daily Speaking Pada Anak-Anak Di Desa Salaon Toba Kabupaten Samosir - Prayuda, Meikardo Samuel (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The development of Samosir as a tourist destination has focused on international development. This is good news for the people of Samosir. This will have an impact on increasing opportunities in the economic sector of the community in Samosir. One of the skills required is language proficiency. Through this, it is hoped that children living in Samosir will be able to understand the importance of international languages and develop enthusiasm to learn more about English. The method for carrying out community service is by using lectures, question and answer sessions, and role playing practices. Through the application of these three methods, participants' enthusiasm for learning English increased. Through the implementation of this service, it can be concluded that the children in Salaon Toba Village show a high level of attention to English language provision. This can be seen from the enthusiasm and interest shown by both the children, who are the objects of this service activity, and the local village head. The positive response can also be seen in the public's interest in this program. At the end of the activity, it was seen that motivation to learn English increased among the children of Salaon Toba Village.